Archer's voice - Sheridan, Mia (2018)
I wanted to lose myself in the small town of Pelion, Maine. To forget everything I had left behind. The sound of rain. The blood. The coldness of a gun against my skin. For six months, each breath has been a reminder that I survived--and my dad didn't. I'm almost safe again. But the moment I meet Archer Hale, my entire world tilts on its axis . . . and never rights itself again. Until I trespass into his strange, silent, and isolated world, Archer communicates with no one. Yet in his whiskey-colored eyes, something intangible happens between us. There's so much more to him than just his beauty, his presence, or the ways his hands communicate with me. On me. But this town is mired in secrets and betrayals, and Archer is the explosive center of it all. So much passion. And so much hurt. But it's only in Archer's silence that we might just find what we need to heal . . . and live.
"With an exclusive extended epilogue!"--Cover.
"First published as an ebook in 2016"--Title page verso.
Keywords: Man-woman relationships -- Fiction; Mute persons -- Fiction; Secrecy -- Fiction; Betrayal -- Fiction; Maine -- Fiction; Love stories; Romance fiction